Treatment of Articular Cartilage Injuries in the Glenohumeral Joint. Issue 3 (September 2018) - McCarthy, Meagan M.; McCarty, Eric
Abstract : Articular cartilage injuries in the glenohumeral joint present a unique and difficult problem for the patient and surgeon alike. Various etiologies exist for the development of these cartilage lesions; therefore, treatment options are vast and must be chosen thoughtfully, especially in the young, active patient. Across all treatment modalities, the goal is for the patient to regain lasting function and mobility while decreasing pain.